NURSING COMPLIANCE IN IMPLEMENTING STANDARD OPERATING PROCEDURES OF PATIENT PREVENTION - Windu Santoso; Taufik Saleh (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Reducing the risk of falling patients is one of the six patient safety goals. To reduce the risk of injury due to falls, the hospital makes the Standard Operating Procedures (SPO) prevention of patients fall as a reference to avoid Unexpected Event (KTD). One of the factors influencing the implementation of SPO is nurse compliance. The purpose of this study to determine the compliance of nurses in implementing standard operational procedures prevention of patients fall in the installation of inpatient hospital Leprosy Sumberglagah. The population in this research were all nurses in the installation of input hospitals Sumberglagah which amounted to 30 nurses, using total sampling technique and sample amounted to 30 nurses. This research uses an observation sheet instrument with 23 statements and is done in 2 weeks. The results of this research indicate that all nurses do not adhere to the Standard Operating Procedures (SPO) prevention of falling patients, of which 30 nurses (100%) in implementing prevention of patients fall out of SPO, either at low risk SPO or medium and high risk. Non-understanding of nurses on the instructions to be the cause of falling nurses on the implementation of SPO prevention of patients fell. In addition, attitude, age, employment and education factors also affect non-compliance of nurses